Achievement of Productive Age Indicator SPM at Bukit Sangkal Health Center, Palembang City - Arisanti, Nova Jane; Jasmine, Annisah Biancika; Rizki, Rizki; Putri, Lydia Atica; Ramadhani, Natasha; Azizah, Nurhalimah; Shakira, Nafisah; Harmadi, Harmadi; Adhiani, Sylvia; Agustini, Meta (Universitas Ibn Khaldun Bogor, 2025)
Health services for individuals in productive age (15–59 years) are a crucial element in the Minimum Service Standards (SPM) for the health sector. The purpose of this study was to assess the achievement of SPM indicators for the Productive Age group and to identify the prevalence of Non-Communicable Diseases (NCDs) at the Bukit Sangkal Health Center, Palembang City. Using a quantitative descriptive approach, data were taken from the Bukit Sangkal Health Center during the period of January to December 2024. This study involved an analysis of the number of visits for health checks and the distribution of NCD cases among the Productive Age group. The findings showed that the SPM target set at 100% was successfully achieved, indicating success in the early detection program and regular health checks. However, the prevalence of NCDs remained high, with Hypertension reaching 2,120 cases, Diabetes Mellitus 303 cases, and Obesity 47 cases, making them the most commonly recorded diseases. The discussion emphasized that these quantitative achievements do not fully reflect the success of the program if they are not accompanied by continuous follow-up, education, and behavioral change. The conclusion of this study is that although the target of achieving SPM has been achieved, health problems among the Productive Age group are still very significant and require a comprehensive and sustainable approach to reduce the burden of NCDs in society.